Comparison of nonlinear growth models and factors affecting body weight at different ages in Toy Poodles. Issue 1 (14th December 2020) - Menchetti, Laura; Padalino, Barbara; Brasileiro Fernandes, Fabienne; Nanni Costa, Leonardo
Abstract: Limited information is available to evaluate optimal growth in Toy Poodles. This work aimed at comparing three growth curves, proposing centile charts and developing a model to estimate the adult body weight (BW) in Toy Poodles. A total of 65 puppies (male = 30, female = 35) born in the same breeding centre were used. BW at birth and, weekly BW, for 53 weeks, BW of parents, litter size, type of management, daily activity and neutering were recorded. Forty-six puppies were sold, and their data were reported by the new owners. Three growth curves (i.e. Hawthorne, Brody and Gompertz) were constructed and compared; Linear Mixed Models including demographic characteristics and management habits were built. The BW at birth was 154 ± 35 g and adult BW was 3208 ± 860 g. Based on the goodness-of-fit and accuracy indices, Gompertz was the best growth model and was selected to plot centile curves based on sex. Toy Poodles achieved 50% of their adult weight at 11–12 weeks, with an overall growth rate of 11.8%. Adult BW was affected by birth BW ( p < .01), sex ( p < .05) and mother's BW ( p < .01) and their effects varied depending on the age. Extrinsic factors, including litter size, type of management and daily activity were less significant, probably due to the standardised and high-level management of these Toy Poodles. These new and applicable tools for monitoring the growth and predicting adult BW could be useful for veterinarians, breeders and owners for early diagnosis of poor health and welfare. Subject classification codes: companion animals sections Highlights: Performance of three logistic models for describing the growth curve in Italian Toy Poodles were compared Based on the goodness of fit and accuracy indices, Gompertz was the best growth model The centile growth curves were constructed for males and females using the Gompertz Adult body weight (BW) was mainly affected by the sex and birth BW, and less by BW of the parents and litter size Monitoring BW of puppies may be useful to enhance their health and welfare